Design and Development of an IoT-Based Prototype System for Monitoring the Care of Dendrobium Orchids - Ahshonat Khoerunnisa; Aan Eko Setiawan; Azwar Mudzakkir Ridwan; Alma Nurshiyami; Siti Hardianti Yuningsih (CoreID Journal, 2025)
The Dendrobium orchid (Dendrobium spp.) is widely appreciated for its beauty and durability in the horticultural industry. To ensure optimal growth, continuous monitoring of environmental conditions is essential. This research presents an Internet of Things (IoT)-based monitoring system that observes real-time temperature, humidity, and soil moisture levels around the orchid. The system utilizes a DHT22 sensor for measuring air temperature and humidity and a soil moisture sensor for detecting the moisture content of the growing medium. An ESP32 microcontroller processes the sensor data and transmits it to the Ubidots cloud platform for real-time visualization. Testing showed that the sensor system achieved an accuracy rate of 4%. Data consistency between the serial monitors and the cloud was maintained, except when network disruptions occurred. This system allows users to remotely monitor critical parameters necessary for orchid health, facilitating better decision-making and timely intervention, ultimately improving the effectiveness of orchid care and maintenance.